From Jihad Resolution to Religious Nationalism: The Role of Islamic Boarding Schools in Strengthening Indonesia’s National Spirit - Fahsin, Moh; Karim, Abdul; Sujadi, Sujadi (EDUKASIA, 2026)
This study explores how Islamic boarding schools (pesantren) in Indonesia have evolved from the era of the 1945 Jihad Resolution to their present role in reinforcing religious nationalism. The research focuses on the ways of pesantren nurturinge the moral, intellectual, and patriotic character of Muslim communities. Using a qualitative descriptive approach supported by historical and literature-based analysis, this study examineds key documents and academic works related to the Jihad Resolution and the development of Islamic education. The results indicated that pesantren were not only active in the struggle for independence through the mobilization of santri and kyai, but also cultivated a spiritual form of nationalism that tied religious devotion to love of the homeland. This legacy later developed into a model of religious nationalism that promotes moderation, pluralism, and civic ethics. Overall, pesantren remain essential institutions in preserving Indonesia’s national identity and social harmony amid contemporary challenges.